INOVASI DALAM PENGEFISIENSI ENERGI MELALUI PERANCANGAN SMART BUFFER CONVEYOR (SBC) LINE SPS - I Ketut Yogi Swarananda; I Gusti Putu Suryawan (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Universitas Mahasaraswati Denpasar, Bali, Indonesia, 2024)
The rapid advancement of technology and information has driven various industries to implement automation systems to improve efficiency and monitor production output. One of the tools used in the production process is the conveyor, a machine in the form of a transport belt that moves products from one stage to another. However, during product overflow or downtime, the conveyor continues to operate, leading to energy waste. This study aims to develop an innovative system that can regulate conveyor movement based on demand, thereby optimizing energy consumption. The research results show that by adding sensors and controlling the system through a PLC, the conveyor's movement can be adjusted: when the product flow is full, the conveyor operates normally; when product flow decreases, the conveyor speed is reduced; and when production stops, the conveyor switches to standby mode. Using 10 conveyor motors can save 1.8 kW of energy, while using 5 conveyor motors can save up to 2.2 kW. This system has been proven to enhance energy efficiency with an accuracy level of 81.80%.